PENANGGULANGAN TERHADAP KEGIATAN ILLEGAL FISHING OLEH KAPAL-KAPAL PENANGKAP IKAN ASING DI WILAYAH PANTAI BARAT SUMATERA - Ferdi, Ferdi; Delfiyanti, Delfiyanti (Jurnal Media Hukum, 2010)
The intensity of fishing activity around West Coast Area of Sumatra increased along with the decrease of the fish amount in marine area in other countries. This condition urged foreign fisherman boats to search for a new fishing area including the West Coast Area of Sumatra. This Area was the strategic part of marine area of Indonesia, it directly faced the high seas, Indian Ocean. Based on the data from Department of Maritime Affairs and Fisheries, marine fishery source of Indonesia was estimated to reach 6.167.940 tons per year. This illegal fishing was certainly detrimental for the country since it threatened the fishery potentials and the fish stock was decreasing. The line of West Coast Area of Sumatra was prone with illegal fishing, which included West Sumatera, Nanggroe Aceh Darussalam, and North Sumatera. The illegal fishing activities in the West Coast of Sumatra had been apprehensive, because the waters around this area were the open sea easily entered by foreign boats. Therefore, âFishery Courtâ (in Medan) was formed to investigate, adjudicate, and decide criminal offense in fishery. The fishermen caught and arrested were then processed further based on the law referring to the Act No. 8 of 1981 on KUHP. Key Words: The Tackling, Illegal Fishing, West Coast Area of Sumatra